REALITA PENERAPAN KEBIJAKAN FISKAL DAN MONETER DI INDONESIA DAN PERMASALAHANNYA - Fahrika, Andi Ika; Ashari, Aisyah; Ansar, Sultan (AL-IQTISHAD: Jurnal Ekonomi, 2023)
This journal discusses Indonesia's Fiscal and Monetary Policy. The problem in this journal is regarding policy enforcement. The type of research used is library research. This study uses a qualitative approach with the aim of examining more deeply the existing social phenomena. In this research using reference books, journal articles and lecture material related to the discussion in this journal.In Indonesia, the government and the central bank collaborate to create policies in fiscal and monetary terms that have an impact on financial stability, inflation, or growth in the economic sector. State revenues or expenditures, which are regulated in the Law on the State Expenditure Development Budget, as well as tax measures to increase state revenues, are some of the fiscal policies that apply in Indonesia. In contrast, BI enforces monetary policy in Indonesia with tools such as interest rates, statutory reserves, and open market operations. However, there are several obstacles to the implementation of effective fiscal and monetary policies in Indonesia, including the lack of coordination between the government and the central bank and the lack of public awareness of the importance of financial stability and the results of fiscal and monetary policies. monetary policy. Thus, there is a need for systematic reforms to encourage public participation in sustainable Indonesian economic development.Keywords: Policy, Fiscal, Monetary.